Functional outcome of proximal femoral nailing for unstable intertrochanteric fracture in elderly - Jose, Ankit; Nazareth, Edward; D'Almedia, Vivian Roshan; Challahalli Rudregowda, Mohan Kumar (International Journal of Research in Orthopaedics, 2020)
Background: This study is intended to analyse the functional outcome of proximal femoral nailing (PFN) for unstable intertrochanteric fractures in elderly. Methods: The data was collected from the 35 patients with unstable intertrochanteric femur fracture who were subjected to PFN from 2015 to 2018. All patients were followed up at 3 months and 6 months after the operation to check the functional outcome based on harris hip score (HHS) and complication if any. Result: In 35 patients, 1 patient was lost to follow-up and 34 patients were followed-up at 3 months and 6 months. All patient’s union was achieved at 3 and 6 months follow up. The cause of fractures was trivial fall in all 35 patients. No incidence of non-union and delayed union was reported. Functional outcome was rated as per HHS, we got excellent results in 20 cases, good in 10, fair in 03 and poor in one patient at end of 6 months. Conclusions: PFN provides stable fixation and early post-operative mobilization with fracture union especially complex proximal femoral fractures which includes unstable, communited, reverse oblique fractures and fractures in osteoporotic bones. PFN has shown excellent results in our study.